Chainsaw man, volume 2 ebook Chainsaw vs. bat. - Fujimoto, Tatsuki (Chainsaw Man, 2020)
In order to achieve the greatest goal in human history—to touch a boob—Denji will risk everything in a fight against the dangerous Bat Devil. But will getting what he wants actually make him happy...?... Rated:T+